1992
DOI: 10.1590/s0074-02761992000400014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the molluscicidal property of Euphorbia splendens var. Hispolii (N.E.B.) (Euphorbiaceae): 2. Investigation in lotic habitat

Abstract: The latex of Euphorbia splendens var. hispolii in 12 ppm concentration (12 mg/l) caused 100% mortality for a Biomphalaria tenagophila population in a lotic habitat after 9 hr of dripfeed application. For sentinel snails, in cages placed at the water surface and buried under 0.10 m, the mortality rates varied with the distance from the application point and were: 100% (0 m); 92.6% (50 m) and 94.7% (100). No lethal effects were observed for the other living species in this habitat (Pomacea haustrum and Poecilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…hislopii latex showed high activity in a field situation makes it a promising natural molluscicide. The result is in accord with Mendes et al (1992Mendes et al ( , 1997 and Baptista et al (1992), who have tested the latex in lentic and lotic environments, respectively, in concentrations between 5 and 12 mg/l against intermediate hosts of Schistosoma mansoni, where they also found 100% mortality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…hislopii latex showed high activity in a field situation makes it a promising natural molluscicide. The result is in accord with Mendes et al (1992Mendes et al ( , 1997 and Baptista et al (1992), who have tested the latex in lentic and lotic environments, respectively, in concentrations between 5 and 12 mg/l against intermediate hosts of Schistosoma mansoni, where they also found 100% mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Now, for Pomacea sp., the mortality rate was lower (40%), also observed by Mendes et al (1992) and Baptista et al (1992), which indicates that this species is more resistant to the molluscicide than M. tuberculata, since both of them contain an operculum that can remain closed for as long as adverse conditions to the means persist. With regard to the toxicology of E. splendens var.…”
Section: Discussionmentioning
confidence: 68%
“…The resistance of Pomacea sp., "shes (Poecilia reticulata), and insect larvae (Odonata) to the biocidal e!ects of E. milii latex was also noted in "eld studies performed by Baptista et al (1992) and Mendes et al (1992). Baptista et al (1992) reported that whereas application of E. milii latex killed 100% of B. tenagophila snails in the test area, Pomacea haustrum snails and P. reticulata "shes found in the same habitat were not a!ected by this plant molluscicide. The resistance of P. haustrum and Odonata larvae to latex-induced lethality was also noted by Mendes et al (1992).…”
Section: Discussionmentioning
confidence: 67%
“…Field studies with aqueous solutions latex were performed by Mendes et al (1992), Baptista et al (1992) and Schall et al (2001) that demonstrated 100% of mortality for Biomphalaria species.…”
Section: Discussionmentioning
confidence: 99%